Bean, Frank D., Susan K. Brown y James D. Bachmeier (2015), Parents without papers: The progress and pitfalls of Mexican-American integration, Nueva York, Russell Sage Foundation - Torre Cantalapiedra, Eduardo (Estudios Demográficos y Urbanos, 2018)
Bean, Frank D., Susan K. Brown y James D. Bachmeier (2015), Parents without papers: The progress and pitfalls of Mexican-American integration, Nueva York, Russell Sage Foundation.